ANALISIS RASIO PROFITABILITAS PADA PT. SUMBER ALFARIA TRIJAYA, TBK (ALFAMART) - Nusale, Grimaldy E. J; Mangindaan, J. V; Mukuan, Danny D. S (JURNAL ADMINISTRASI BISNIS, 2017)
To assess whether or not the company's healthy performance lies in its financial performance. To know the level of achievement or success of the company, then the necessary financial indicators. These financial indicators can be obtained from financial statements. The financial statements used are balance sheet and income statement. To find out how far the development of the company from year to year required an analysis. The most important aspect in analyzing financial statements is profitability, as a measure of management effectiveness indicated by the profit generated from the sale of corporate investment. An analysis tool that can be used to measure the success rate of a company in generating profit is to use profitability ratio analysis. The purpose of this study is to determine the financial performance of PT. Sumber Alfaria Trijaya, Tbk reviewed from profitability ratios. Sunyoto (2013) profitability ratio is the ability to profit from its business. Financial performance analysis tool based on profitability ratios used in this study is RETURN ON ASSET, RETURN ON EQUITY, MARGIN PROFIT NET AND GROSS PROSIT MARGIN from 2012 – 2015. Based on the results of the analysis it has been seen that the average RETURN ON ASSET is 5%, below the industry standard average of 20% and return on equity has a downward trend where the average RETURN ON EQUITY is 16 , 60% is still below the industry standard average of 30% and net profit margin is 18.15% is still below industry standard and the result of Gross Profit Margin always increases , The average GROSS PROSIT MARGIN showed poor results because only 1.48% was still below the industry average of 20%. This research is expected to enrich the concept of knowledge about Profitability ratio analysis. The results of this study are expected to provide meaningful information to the management of the company regarding the position of Profitability of the company. Key Word : Ratio Profitability